Microglial genes regulating neuroinflammation in the progression of Alzheimer's disease. (February 2016) - Villegas-Llerena, Claudio; Phillips, Alexandra; Garcia-Reitboeck, Pablo; Hardy, John; Pocock, Jennifer M
Highlights: Microglia are the immune cells of the CNS. Microglial reactivity has been implicated in the pathogenesis of Alzheimer's disease. We know considerably more about the genetic link between early-onset AD than late-onset AD. Recent GWAS have highlighted gene mutations linked to enhanced risk of LOAD, and which code for proteins expressed in microglia. This review discusses these recent findings and the implications for microglial reactivity in AD. Abstract : Neuroinflammation is a pathological hallmark of Alzheimer's disease (AD), and microglia, the brain's resident phagocyte, are pivotal for the immune response observed in AD. Microglia act as sentinel and protective cells, but may become inappropriately reactive in AD to drive neuropathology. Recent Genome Wide Association Studies (GWAS) have identified more than 20 gene variants associated with an increased risk of late-onset AD (LOAD), the most prevalent form of AD [1 ]. The findings strongly implicate genes related to the immune response (CR1, CD33, MS4A, CLU, ABCA7, EPHA1 and HLA-DRB5-HLA-DRB1), endocytosis (BIN1, PICALM, CD2AP, EPHA1 and SORL1) and lipid biology (CLU, ABCA7 and SORL1) [2–8 ], and many encode proteins which are highly expressed in microglia [1 ]. Furthermore, recent identification of a low frequency mutation in the gene encoding the triggering receptor expressed in myeloid cells 2 protein (TREM2) confers increased risk of AD in LOAD cohorts with an effect size similar to that for APOE, until recently the only identified genetic risk factor associated with LOAD [9, 10 ] (Figure 1). The present review summarises our current understanding of the probable roles of microglial genes in the regulation of neuroinflammatory processes in AD and their relation to other processes affecting the disease's progression.Current Opinion in Neurobiology 2016, 36 :74–81 This review comes from a themed issue onNeurobiology of disease Edited byDennis J Selkoe andDaniel R Weinberger For a complete overview see theIssue and theEditorial Available online 24th October 2015 http://dx.doi.org/10.1016/j.conb.2015.10.004 0959-4388/Published by Elsevier Ltd.